Plastic cover usage in reducing soil erosion loss / Zainal A. Gani - A. Gani, Zainal (1997)
Recently soil erosion has become a very serious problem in Malaysia and will continue to enhance the problem in the future, unless proper planning and administration of the utilisation of land is adopted at early stage. The prevention of soil erosion, which means reducing the rate of soil loss to approximately that which would occur under natural condition, relies on selecting appropriate strategies for soil conservation and this in turn, requires a thorough understanding of the process of erosion. The factors which influences the rate of erosion are rainfall, runoff, wind, soil properties, topography, slope vegetation and the presence or absence of conservation measures. Primary objective of soil conservation works must be control and reduce erosion. Using plastic cover to protect erosion loss is one solution to an erosion problem. This plastic cover is one of the protection works but its may not be necessary to the solution of an erosion problem. There may be one solution but it is not necessarily the best In this research, plastic cover can reduce about 84.46 % of soil erosion loss